The Effect of Using A Computer Assisted Instruction (CAI) About Nursing Care of Critical Patients with Intercostal Drainage Toward Knowledge of Professional Nurses in Police General Hospital - ทองดี สิริพร (Journal of The Royal Thai Army Nurses, 2019)
The purposes of this study were to 1) compare knowledge of professional nurses about critical patients with intercostals drainage (ICD) in an experiment group of profession nurses before and after using a computer assisted instruction (CAI),2)compare knowledge of professional nurses about critical patients with ICD in experiment group and a control group, and 3) study satisfaction of professional nurses influence using CAI. The samples were purposive selection twenty critical professional nurses in Police General Hospital. They were divided into two groups by simple random sampling. The experimental group 10participants received CAI and control group 10participants received normal teaching. The instruments were 1) CAI about nursing care of critical patients with ICD,2) test of knowledge about nursing care of critical patients with ICD, and 3) questionnaires of satisfaction for professional nurses using CAI. The statistics were percentage, mean, median, quartile deviation, standard deviation, Wilcoxon Signed Rank test, and Mann-Whitney U test. The research results were:1) the experiment group after using CAI had higher median of knowledge about critical patients with ICD than before using CAI and statistically significance at .01 level,2) The experiment group of professional nurses had higher median of knowledge of professional nurses about critical patients with ICD than the control group and statistical significance at .01 level, and 3) The professional nurses had overall satisfaction the CAI about critical patients with ICD in high level. Therefore, new critical professional nurses should be encouraged to be taught and review knowledge with CAI along with practice in order to increased knowledge of nursing care.